Remarques sur un aspect quantitatif de la phraséologie comparée - Bogacki, Krzysztof (Wydawnictwo Naukowe UAM, 2003)
Phraseology provides a convenient way to study conceptual images of things, animals, phenomena etc. as they characterize different cultures and civilizations. On the other hand, the comparison of idioms with nouns of animals in two languages makes possible the calculus of numerical indices which can be used to measure the degree of intensity of isomorphism in the two compared lexicons.
Remarks on the quantitative aspect of comparative phraseology
Keywords: Comparative phraseology